Os serviços colaborativos da economia compartilhada e as transformações na noção de confiança nas interações e práticas de consumo nas redes sociais digitais: uma cartografia dos processos de criação na cultura - Marassi, Alessandra de Castro Barros (2018)
The present doctoral thesis develops cartography of the creation processes in the network culture that grounds the shared economy services. The thesis affirms that these services are based on the building of trust links and has as research question to investigate the transformations of the notion of trust in the interactions and practices of consumption present in digital social networks. The cartography was developed in three stages: (1) the choice of platforms of services of shared economy; (2) analysis of system characteristics, testing and experimentation and study of user experience reports with collaborative network services; (3) cartography of the dynamics of confidence building and proposition of values that establish the norms of operation of the services. The use of shared economy platform services, inserted in the network culture, operates through logics linked to the process of confidence building. This process starts from the verification of the evaluations of other users, in addition to the recommendations and testimonies recorded on the Internet. The interactions that occur in the services into in the collaborative economy demand trust between unknown individuals. Interactions, interrelationships, and evaluation systems play the role of regulation and serve as a device for the process of building trust. The research conducted three case studies: BlaBlaCar, the carpool application; the social networks to hospitality services: Couchsurfing and the Trusted House Sitters. The applied method involved multidisciplinary bibliographic research; qualitative research and development of cartography of the chosen networks (Leo). In cartography, in addition to actual experimentation and analysis of the systems and their operations, we searched for user reports and performed qualitative interviews. The theoretical basis is composed by cyberculture authors such as (Lemos, Leão and Levy); research on networks, communication and power (Foucault and Castells) and consumption and collaboration (Botsman). As results obtained, our research developed a diagram and systematized propositions for the trust construction in the contract of services of sharing in digital social networks